1994
DOI: 10.1080/00288330.1994.9516603
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of faecal streptococci from some New Zealand effluents and receiving waters

Abstract: Different proportions of component species of faecal streptococci were found in New Zealand sewage, animal processing effluents, and animal faeces. Enterococcus faecium was the major species in raw sewage (43-65%), followed by E.faecalis (19-40%) or E. durans (14-23%). Meat processing effluent usually had a higher proportion of f. durans (37-73%) than sewage. Enterococci, mainly E. durans (34%), dominated in sheep faeces, but Streptococcus bovis comprised 53% of the faecal streptococci in cattle faeces. In sew… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
17
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 27 publications
6
17
0
Order By: Relevance
“…were the predominant fecal coliforms. These results are in agreement with previous studies (Brown and Tracey, 1975;Hill and Sobsey, 1998;Laukova and Juris, 1997;McLellan et al, 2001;Sinton and Donnison, 1994;Svec and Sedlacek, 1999;Vilanova et al, 2004). E. coli was the main fecal coliform in any kind of the studied samples.…”
Section: Discussionsupporting
confidence: 83%
“…were the predominant fecal coliforms. These results are in agreement with previous studies (Brown and Tracey, 1975;Hill and Sobsey, 1998;Laukova and Juris, 1997;McLellan et al, 2001;Sinton and Donnison, 1994;Svec and Sedlacek, 1999;Vilanova et al, 2004). E. coli was the main fecal coliform in any kind of the studied samples.…”
Section: Discussionsupporting
confidence: 83%
“…These results probably reflect well-recognized differences in species composition. The fecal streptococci include S. bovis, which comprised over one-half the fecal streptococci in fresh cow pats on nearby farms (32). Studies reviewed by Sinton et al (33,34) have shown that the S. bovis-S. equinus group is more rapidly inactivated in the environment than the enterococcal species E. faecium and E. faecalis.…”
Section: Fig 4 Survival Of E Coli (E) Fecal Streptococci (F) Entmentioning
confidence: 99%
“…The selected indicators were E. coli, fecal streptococci, and enterococci. Fecal streptococci were included in addition to enterococci because a previous survey showed that Streptococcus bovis (a non-Enterococcus species) comprised over one-half of the fecal streptococci in local cattle feces (32). The selected pathogens were Salmonella enterica and Campylobacter jejuni.…”
mentioning
confidence: 99%
“…In sewage, faecal streptococci tend to be present in concentrations 10-100 times less than faecal coliforms (Sinton et al 1993b;Sinton & Donnison 1994). In contrast, faecal streptococci in animal faeces generally outnumber faecal coliforms-up to 10 7 per g in sheep faeces and 10 6 in cow faeces (Mara 1974;Sinton etal.…”
Section: Presence In Faeces and Effluents And Survival In Watermentioning
confidence: 99%